Apolipoprotein E polymorphism is associated with both number of diseased vessels and extent of coronary artery disease in Czech patients with CAD - Machal, Jan; Vasku, Anna; Hlinomaz, Ota; Linhartova, Petra; Groch, Ladislav; Vitovec, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2012)
AIMS: The impact of ApoE polymorphism on angiographic parameters was assessed in patients referred for coronary angiography. METHODS: Elective coronary angiography was performed in 671 subjects (525 men, 146 women, mean age 60 ± 10 years) with symptoms of ischemic heart disease. The patients were divided into: no CAD group (smooth coronary vessels, n=83), one-vessel (n=155), two-vessel (n=170) and three-vessel disease (n=196). Patients with stenoses 0-50% were excluded. Within patients with CAD, we evaluated overall extent of CAD measured by the number of stenotic segments according to AHA (1 segment vs. 2-3 vs. ≥4), and the severity of the most serious stenosis (in percent). ApoE genotype was determined using real-time PCR. RESULTS: The frequency of ε2/ε3 genotype (n=56) was lower in the three-vessel disease group compared to one-vessel disease (OR=0.25, P=0.0019), two-vessel disease (OR=0.31, P=0.0114) or no CAD group (OR=0.24, P=0.0057). Frequency of ε2/ε3 decreased with the number of affected segments (1 vs. ≥4: OR=0.35, P=0.0143). The ε3/ε4+ε4/ε4 genotypes (n=123) were more frequent in CAD patients altogether compared with no CAD group (OR=2.30, P=0.019), while no impact of the ε4 allele on angiographic parameters within the CAD patients was detected. In ε2/ε3 carriers with CAD, lower LDL-cholesterol, total cholesterol and lower use of lipid-lowering drugs were observed. CONCLUSIONS: The results show predominantly focal form of CAD in patients with ε2/ε3 genotype. Lower LDL-cholesterol and total cholesterol may play the key role, although other contributing factors are discussed.
Keywords: Coronary Angiography; Humans; Apolipoproteins E; lidé středního věku; Middle Aged; Genotype; nemoci koronárních tepen; Polymorphism, Genetic; Coronary Artery Disease; mužské pohlaví; polymorfismus genetický; Cholesterol; apolipoproteiny E; ženské pohlaví; genotyp; lidé; Aged; senioři; Male; koronární angiografie; cholesterol; Female